Analyzing The Grief of Naomi in The Book of Ruth - Sia Kok Sin (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2022)
This article analyzed the grief of Naomi in the book of Ruth by using the six stages of grief by Elisabeth Kübler-Ross and David Kessler. Although Naomi could be an inadequate model in dealing with her grief, her attitude resonates with many people in dealing with their griefs. It makes this study is noteworthy. This article analyzed how Naomi dealt with her grief in the six stages of grief, namely: denial, anger, bargaining, depression, acceptance, and finding the meaning and then take the implication for the ministry during the pandemic of Covid-19. The study showed that anger and depression are visible in the story of Naomi. Acceptance is not explicit. There is no denial, bargaining, and finding the meaning stages in Naomi’s grief. She was still struggling with her grief, although she could accept the new situation with the marriage of Ruth and Boaz and the birth of Obed. Today many people struggle with grief during this pandemic. Therefore, it is essential to pay attention to vaccines and medication and notice the need for psychological help and therapy for the bereaved families.